Vestibulospinal system findings caused by ageing between 40 and 55 years. (2nd October 2022) - Konukseven, Ozlem; Satici, Sema; Adali, Inci; Yildiz, Yagmur; Dogru, Lena; Duruoglu, Sencan
Abstract: Objective(s): In this study, it was aimed to evaluate the weakness in postural balance skills that occurred between the ages of 40–55 by comparing vestibulospinal tests and static posturography tests. Methods: A total of 40 healthy individuals between the ages of 18–30 (mean: 23.8 ± 3.05 years) and 40–55 (mean: 49.2 ± 6.4 years) who voluntarily agreed to participate in the study, without vertigo and balance problems were included. As being objective vestibulospinal tests, the modified clinical test of sensory interaction and balance (mCTSIB) and Limits of Stability (LOS) tests were performed using a static posturography device. Tandem Romberg, Fukuda Stepping Test (FST) and Babinski–Weil tests were performed as subjective vestibulospinal tests. Results: Compared with the younger group, 40–55 ages showed significant weakness in movement velocity (MVL), endpoint excursions (EPEs), maximum excursions sub-parameters of LOS, in all eyes-closed subtests in the mCTSIB test, and in subjective vestibulospinal tests. No relationship between vestibulospinal and static posturography was observed. Conclusions: Contrary to popular belief, the effect on the age-related balance system begins earlier. When the middle age group applies to ENT clinics with complaints of imbalance, it should be taken into account that age-related effects may occur.